2016
DOI: 10.1177/0734282916670797
|View full text |Cite
|
Sign up to set email alerts
|

Informant Discrepancies in the Assessment of Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is characterised by developmentally inappropriate levels of hyperactivity, impulsivity, and/or inattention, leading to significant impairment across multiple domains of functioning. To receive a diagnosis, symptoms must be present across two or more settings; thus requiring information to be collected from multiple informants, typically parents and teachers. Research consistently shows low to moderate agreement between parent and teacher reports; however, mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…In order for a diagnosis of ADHD to be made, the behaviors and symptoms may not solely be a manifestation of oppositional behavior, defiance, hostility, or failure to understand tasks or instructions [13]. The true prevalence of ADHD is challenging to measure as diagnosis is dependent on individual interpretations of behavior as well as the manner in which a clinician integrates multiple informant reports from parents, caregivers, and teachers [17]. Additionally, the reliability of one individual's self-report of their ADHD symptoms in adolescence and adulthood may be inconsistent with multiple-informant reports [18].…”
Section: Disruptive Behavior Disorders and Adhd: Prevalence Disparitmentioning
confidence: 99%
“…In order for a diagnosis of ADHD to be made, the behaviors and symptoms may not solely be a manifestation of oppositional behavior, defiance, hostility, or failure to understand tasks or instructions [13]. The true prevalence of ADHD is challenging to measure as diagnosis is dependent on individual interpretations of behavior as well as the manner in which a clinician integrates multiple informant reports from parents, caregivers, and teachers [17]. Additionally, the reliability of one individual's self-report of their ADHD symptoms in adolescence and adulthood may be inconsistent with multiple-informant reports [18].…”
Section: Disruptive Behavior Disorders and Adhd: Prevalence Disparitmentioning
confidence: 99%
“…For instance, Kennerley et al (2018) investigated parent and teacher ratings of attention-deficit/hyperactivity symptoms and compared those ratings with observations made by a clinician at school. The teacher ratings, but not the parent ratings, of the total symptoms correlated with the respective observer ratings.…”
Section: Reasons For Weak Agreement and Strong Discrepancy Between mentioning
confidence: 99%
“…Previous research has generally found that parents report higher levels of ADHD symptoms (e.g. Antrop et al, 2002;Hart et al,1995;Kennerley et al, 2016;Murray et al, 2007;Narad et al, 2015;Yeguez & Sibley, 2016), although there have also been some cases where teachers have reported higher levels (e.g. Jester et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is known from cross-sectional analyses that cross-informant discrepancies in psychopathology, including ADHD symptoms, abound (e.g. Achenbach, 2005;Kennerley et al, 2016). Discrepancies are also seen in the substantive conclusions of research studies with, for example, significant associations or treatment effects observed according to one informant but not another (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation